INFLUENCE OF TEMPERATURE ON STABILITY OF ALUMINUM FOAM CELL WALL DURING FOAMING PROCESS - Rabie, Fatthie Khairullah Hishyam (IRC, 2016)
This work reports the influences of foaming temperature on the behavior of aluminum cell wall during foaming process. Pure aluminum powder with reacting agent, Titanium Hydride (TiH2) are main components on this project where the hydrogen gas that trap inside the foaming die during foaming process producing pores. Three scopes being highlighted in this project which are metal foam in powder metallurgy process, observation of cell wall and porosity, and hardness and compression strength of aluminum foaming. There are four major temperatures being experimented which are 750°C, 800°C, 850°C and 900°C with constant foaming time, five minutes. Observation has being made using optical microscope (OM) and scanning electron microscope (SEM).